FEDERAL TECHNOLOGICAL EDUCATION CENTER FROM CAMPOS STUDENTS` DISSATISFACTION WITH THE BODYIMAGE ACCORDING TO THE SCHOOLLEVEL (Fiep Bulletin - online, 2013)
The mental image is made from the integration of several sensory modalities and several psychic processes which are usually exchanging (TAVARES, 2003), then, as the social and cultural aspects, which are also determining for the build, evolving continually lifelong. The sociable benefits are related to the insertion of this subject in such this society which emphasizes the desire. The body roles the play of stimulating the “narcissism” culture, when the prosthesis offered by the compulsive society are necessary for the subject to fill in evidence, what means that he exists (CARRETEIRO, 2005). So, the present study proposes to show topics to identify the levels of satisfaction with the body image among the students from Federal Technological Educational Center from Campos dos Goitacazes according to their school levels. The data gotten had been studied trough descriptive and inferential statistics. Using for the first, references about averages, variance, pattern deviation and others statistics when necessary. ANOVA unique fact has been used for the inferential analysis. 300 students have been studied, being 100 from high school (EM), 100 graduation (ES) and 100 postgrade (PG). Facing the presented data, we can conclude that, there are no indicators of dissatisfaction with the body image, but we must pay attention to the increasing of dissatisfaction with the body image, mainly among the girls and women, by their graduation and the ones submitted to the tests.
Keywords: body image; aesthetics; School Physical Education